Clinical Observation: Congenital Absence of the Left Portal Vein in a Patient Undergoing Hepatic Resection. Issue 5 (1997) - Charny, C. K.; Ling, P.; Botet, J.; Blumgart, L. H.
Abstract : Congenital absence of the left portal vein is a rare vascular anomaly with a reported prevalence varying from one in 62 to one in 507 cases. A patient admitted for recurrent cholangitis secondary to extensive dilation of the left biliary ductal system associated with Caroli's Disease was determined by preoperative dynamic CT to have an excessively large right portal vein and no left portal vein. The surgeon must be aware of any variations in portal vascular anatomy in patients undergoing hepatic resection in order to prevent potentially fatal postoperative complications.